Sexual knowledge based on Islamic values and sexual risk behaviors of HIV/STIs among Thai Muslim army conscripts: A cross-sectional study - Awirut Singkun; Kraiwuth Kallawicha; Khemika Yamarat (Belitung Nursing Journal, 2022)
Background: Sexually transmitted infections (STIs), including human immunodeficiency virus (HIV), are commonly associated with conflict areas. In Thailand, conflict situations have occurred from 2004 until the present in three Muslim-majority southernmost provinces, including Yala, Pattani, and Narathiwat. However, Islam provides strict guidelines on sexuality. Therefore, those who strictly practice Islam will have lower sexual risk behavior. Objective: This study aimed to examine the relationship between Islamic values-based sexual knowledge, sociodemographic factors, and risk for HIV/STIs among Thai Muslim army conscripts in the unrest situation area. Methods: A cross-sectional study was conducted between May and July 2020. Data were collected using a validated questionnaire among 421 participants. Descriptive statistics and Chi-square were used to examine the association among variables. Results: 57.5% of Muslim army conscripts had poor sexual knowledge based on Islamic aspects, and the participants showed high-risk profiles for HIV/STIs (32.5%). Marital status, hometown, smoking and drinking status, and Islamic values-based sexual knowledge were significantly associated with the risk of HIV/STIs (p <0.05). Conclusion: Participants with poor sexual knowledge according to Islamic values, smokers, single-status, alcoholic drinkers, and non-three southernmost provinces’ hometowns had higher risks of HIV/STIs. Thus, it is suggested that nurses and public health professionals implement sexual health promotion and prevention for HIV/STIs. In addition, misperceptions of Islamic aspects toward sexual behavior should receive immediate adjustments.